Ultrasonic relaxation of TeWB glasses at low temperatures - Saddeek, Yasser B.; Ivanov, V.; Saddek, Amr Bakr; Zakaly, Hesham M. H.; Sidek, H. A. A.; Mahmoud, I. S.; Matori, K. A.; Zaid, M. H. M. (Elsevier, 2021)
The ultrasonic relaxation of tellurite glasses xB2O3 – 70 TeO2 – (30 – x) WO3, 0 ≤ x ≤ 30 mol% was investigated by measuring the ultrasonic attenuation (αL) in these glasses in the thermal range 140–300 K (T) at various frequencies (f). Some characteristics can be obtained from the relation of αL–T, such as the average activation energy (Ep) and the attempt frequency (f0). The variables Ep and f0 are a function of frequency and B2O3 content. Moreover, the relation αL–T accounts well for the oscillations of the oxygen atoms in a relaxation process. Such a physical process is originated from transmitting ultrasonic energy to the oscillating oxygen atoms in a dual-well potential. The relaxation process is inspected by a model named central force one. The subtracted different physical variables from such a model are a function of B2O3 content.